Genomic diversity of the human pathogen Paracoccidioides across the South American continent - Teixeira, Marcus de Melo (2020)
Paracoccidioidomycosis (PCM) is a life-threatening systemic mycosis widely reported in the Gran Chaco ecosystem. The disease is caused by different species from the genus Paracoccidioides, which are all endemic to South and Central America. Here, we sequenced and analyzed 31 isolates of Paracoccidioides across South America, with particular focus on isolates from Argentina and Paraguay. The de novo sequenced isolates were compared with publicly available genomes. Phylogenetics and population genomics revealed that PCM in Argentina and Paraguay is caused by three distinct Paracoccidioides genotypes, P. brasiliensis (S1a and S1b) and P. restrepiensis (PS3). P. brasiliensis S1a isolates from Argentina are frequently associated with chronic forms of the disease. Our results suggest the existence of extensive molecular polymorphism among Paracoccidioides species, and provide a framework to begin to dissect the connection between genotypic differences in the pathogen and the clinical outcomes of the disease.